Anti-leishmanial activities of Olea europaea subsp. laperrinei extracts: Leishmanicidal effect of Olea laperrinei extracts - Lahcene, Souad; Trabelsi, Lamia; M. Salem-Bekhit, Mounir; Shazly, Gamal A.; Mohammed Refat M. Selim, Heba; Mohammed Alehaidib, Soliman; Sebbane, Hillal; Msela, Amine; Benguerba, Yacine; Houali, Karim (Cellular and Molecular Biology, 2023)
Leishmaniasis is an infectious disease that is often fatal in affected patients and represents a major public health problem. At present, no vaccine is available, and the drug treatments used are costly, long, and have numerous side effects, they also present variable effectiveness, frequent relapses, and a more and more marked resistance towards the parasites. Thus, new therapeutic strategies are urgently needed, and they are mainly based on the research of active natural products. The objective of our study is the chemical characterization and the quantification of the polyphenol contents contained in the EAF and EAT extracts of the Laperrine olive tree and the evaluation of their antileishmania effect against Leishmania infantum. The quantification of polyphenols, flavonoids and total tannins shows a higher content in the leaf extract. We find respectively 776.76±30.64 mg gallic acid equivalent/g DR; 114.35±14.12 mg quercetin equivalent/g DR and 214.89±.17 mg tannic acid equivalent/g DR.The chemical characterization of Olea europaea subsp. laperrinei extracts show the presence of numerous antileishmanial biomolecules such as oleuropein, hydroxytyrosol, rutin, gallic acid, cafeic acid, rosmarinic acid, and quercetin.In this context, we are testing the in vitro leishmanicidal effect of Laperrine olive tree extracts. The results obtained are promising and highlight the effectiveness of the tested extracts against the promastigote form of Leishmania infantum. Indeed, the LD50 is obtained with the leaf extract at a concentration of 7.52±2.71 µl/ml.